2015
DOI: 10.3171/2014.12.jns142169
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of corticospinal tract in patients with resected brainstem cavernous malformations using high-definition fiber tractography and diffusion connectometry analysis: preliminary experience

Abstract: abbreviatioNs ADL = activities of daily living; CC = corpus callosum; CM = cavernous malformation; CN = cranial nerve; CST = corticospinal tract; DSI = diffusion spectrum imaging; DTI = diffusion tensor imaging; FDR = false discovery rate; HDFT = high-definition fiber tractography; ICH = intracerebral hemorrhage; QA = quantitative anisotropy; ROI = region of interest; SRS = stereotactic radiosurgery. obJect Brainstem cavernous malformations (CMs) are challenging due to a higher symptomatic hemorrhage rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…36 QA bypasses the limitations of fractional anisotropy (FA) and generalized FA on the areas of crossing fibers, such as the centrum semiovale and the brainstem, and the areas of mass effect originated by a lesion. 12,32 In the case presented here, the quantitative results showed a correlation with the qualitative data of trajectory restoration and tract preservation and with the partial improvement on patient's motor strength.…”
Section: Applications Of Hdft For Intra-axial Brainstem Lesionssupporting
confidence: 67%
See 2 more Smart Citations
“…36 QA bypasses the limitations of fractional anisotropy (FA) and generalized FA on the areas of crossing fibers, such as the centrum semiovale and the brainstem, and the areas of mass effect originated by a lesion. 12,32 In the case presented here, the quantitative results showed a correlation with the qualitative data of trajectory restoration and tract preservation and with the partial improvement on patient's motor strength.…”
Section: Applications Of Hdft For Intra-axial Brainstem Lesionssupporting
confidence: 67%
“…In cases involving noninfiltrative lesions (eg cavernous malformations), surgical resection is facilitated by the fact that the white matter tracts are typically displaced to the periphery of the lesion, while no tracts run within the lesion itself. 12,32 In contrast, in cases of diffuse pathology, such as the glioma presented here, important fiber tracts may be infiltrated in addition to displaced, and located within the confines of the lesion instead of the periphery. In such cases, HDFT not only can help defining the anatomy of the displaced fiber tracts around the lesion but can depict the location of infiltrated fiber tracts that could be placed at risk during the resection and therefore can also help defining the boundaries of a safe resection within the lesion.…”
Section: Applications Of Hdft For Intra-axial Brainstem Lesionsmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, in brainstem cavernomas, the classic perilesional hemosiderin deposits can be responsible for susceptibility artifacts that can falsely interrupt nearby tracts (Faraji et al, 2015, Kovanlikaya et al, 2011). The close proximity of large arteries (vertebral and basilar) can also produce pulsation artifacts (Kovanlikaya et al, 2011).…”
Section: Infratentorialmentioning
confidence: 99%
“…Each of these factors affects surrounding white matter differently. In general, however, it is observed that benign, non-neuronal lesions such as meningiomas and cavernomas cause tract displacement, whereas diffusely proliferating gliomas produce incremental tract infiltration and destruction with increasing histopathological grade [5,[34][35][36] (Fig. 1).…”
Section: Use Of Tractography For Evaluation Of Perilesional White Matmentioning
confidence: 99%